Brain-derived neurotrophic factor Val66Met polymorphism affects cortical thickness of rostral anterior cingulate in patients with major depressive disorder. Issue 16 (4th November 2020) - Shen, Zonglin; Lu, Yi; Jiang, Hongyan; Ye, Jing; Zhou, Cong; He, Mengxin; Li, Na; Xu, Xiufeng; Cheng, Yuqi
Abstract : Objective: The neuro-anatomical substrates of major depressive disorder (MDD) remain poorly understood. Brain-derived neurotrophic factor ( BDNF ) gene polymorphism ( Val 66 Met /rs6265) is associated with neuro-plasticity and development. In the present study, we explore the influence of BDNF gene polymorphism on cortical thickness in nonelderly, first episode, drug-naive patients with MDD. Methods: Two hundred and sixteen participants (105 MDD patients and 111 healthy controls) were divided into subgroups based on the BDNF genotype. High-resolution MRI was obtained in all participants. A relationship of BDNF Val 66 Met gene polymorphism and cortical thickness was investigated. Results: The significant main effect of diagnosis was identified in the left rostal anterior cingulate (rACC), right inferior temporal and right lateral orbitofrontal (lOFC). The main effect of the genotype was observed in the left posterior cingulate cortex. The diagnosis-by-genotype interaction effect was found located in the left rACC. MDD patients who were Met -carriers exhibited thinner cortical thickness in the left rACC than healthy controls Met -carriers. Neither the symptom severity nor the illness duration was correlated significantly with cortical thickness. Conclusion: Our findings suggested that the BDNF gene polymorphism was associated with cortical thickness alterations of the left rACC in MDD patients, and genotype that carries Met may serve as a vulnerability factor in MDD regarding the cortical thickness loss in the left rACC. This finding can be considered as a supportive evidence for the neurotrophic factor hypothesis of depression.